Integration of Higher Education Institutions to Address the Challenges of Regional Socio-Economic Development - Gaponova, Olga S.; Smeltsova, Svetlana V.; Chilipenok, Yulia Yu. (Economy of Regions, 2020)
Recently, the topic of regional development has become particularly relevant since regions are gaining more and more autonomy in solving their socio-economic issues. This transformation results in the concern of how to find potential partners for building a regional development strategy, sharing resources and competencies. In this context, it is advisable to consider universities as a significant potential partner. In particular, it is necessary to analyse their role and capabilities in creating a regional strategy, the most relevant forms of interaction, and indicators for assessing the effectiveness of the universities’ integration to address the challenges of regional development. We applied the expert interview method and discussed the problem with representatives of 28 Russian universities who occupy top managerial positions and have an expert opinion on key issues. Based on the analysis of empirical material, we identified three main roles of universities in regional development: a project initiator, a partner, and a source of human and analytical resources. During the resource assessment, we determined that funding is the only scarce resource for universities, while all other resources and competencies can be quickly mobilised if necessary. The most effective mechanisms for integrating universities to address regional challenges are a consortium of universities and the organisation of project offices with the participation of government and business representatives. The main research result was the identification of quantitative and qualitative criteria characterising the universities’ involvement in solving socio-economic issues of regional development, as well as indicators, which are necessary for their definition. Additionally, we discovered a previously unidentified information and administration group among the quantitative criteria and defined the main stages of assessing the effectiveness of such integration. In regards to the considered issue, a promising direction for further research would be a comparative analysis of the effectiveness of the universities’ integration to address social and economic challenges in different regions of the Russian Federation.